2022
DOI: 10.1002/cpt.2577
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network vs. Pharmacometric Model for Population Prediction of Plasma Concentration in Real‐World Data: A Case Study on Valproic Acid

Abstract: We compared the predictive performance of an artificial neural network to traditional pharmacometric modeling for population prediction of plasma concentrations of valproate in real‐world data. We included individuals aged 65 years or older with epilepsy who redeemed their first prescription of valproate after the diagnosis of epilepsy and had at least one valproate plasma concentration measured. A long short‐term memory neural network (LSTM) was developed using the training data set to fit the LSTM and the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…An additional study used a long short-term memory neural network, a type of artificial neural network, to predict plasma concentrations of valproic acid in older adults and compared this with predicted concentrations from a previously published population PK model. 55 Model performance was assessed by comparing the proportion of individuals with at least one predicted concentration within 620 mg/L of the observed concentrations between the two models. The results showed that the DL model outperformed the population PK model, but further work to improve the predictive performance of this approach was noted.…”
Section: Case Examples Of Ai and ML In Tdm And Mipd Concentration And...mentioning
confidence: 99%
“…An additional study used a long short-term memory neural network, a type of artificial neural network, to predict plasma concentrations of valproic acid in older adults and compared this with predicted concentrations from a previously published population PK model. 55 Model performance was assessed by comparing the proportion of individuals with at least one predicted concentration within 620 mg/L of the observed concentrations between the two models. The results showed that the DL model outperformed the population PK model, but further work to improve the predictive performance of this approach was noted.…”
Section: Case Examples Of Ai and ML In Tdm And Mipd Concentration And...mentioning
confidence: 99%
“…It was concluded that the regression tree performed the best among the machine learning algorithms in both the derivation and testing cohorts. A long short-term memory (LSTM) model was developed to assess its ability in predicting valproate concentrations in older patients with epilepsy [18]. When compared with the population pharmacometrics model of valproate, the developed LSTM model had a better predictive performance in the external evaluation study.…”
Section: Introductionmentioning
confidence: 99%